Leadership Behavior That Affecting To The Effective Personnel Management in school under the office of Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 - Jaroensuk, Prasert; Montaisong, Teerawat (Mahachula Academic Journal, 2024)
The purposes of this research are (1) to study leadership behavior; Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 (2) to study the efficiency of personnel administration operations in educational institutions. Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 (3) to study leadership behaviors that affect personnel management efficiency in educational institutions. Under the Office of Phra Nakhon Si Ayutthaya Primary Educational Service Area, Region 1 The samples used in this research were supervisors or persons in charge of personnel administration of schools under Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1, totaling 123 schools. manage The confidence value was 0.89 and the questionnaire about the efficiency of personnel management in educational institutions. The confidence value was 0.96 Statistics used in data analysis were mean, standard deviation. Pearson's correlation coefficient (r) and multiple regression analysis by the enter method. (Enter) The results of the research revealed that (1) leadership behavior Under the Office of Phra Nakhon Si Ayutthaya Primary Educational Service Area, Region 1, the overall level was at a moderate level. The aspect with the highest mean was team-based leadership behavior, followed by moderate leadership behavior. and the side with the lowest mean was the low-work-oriented, high-people-oriented leadership behavior, respectively. (2) Efficiency of personnel administration in educational institutions. Under the Office of Phra Nakhon Si Ayutthaya Primary Educational Service Area, Region 1 in the overall level was at a high level. The aspect with the highest average was evaluation and performance, followed by personnel development. and the aspects with the lowest average values ​​were the planning and positioning aspects, respectively. (3) The overall leadership behavior had a positive correlation with the efficiency of personnel administration in educational institutions. Overall is low. statistically significant at .01 (4) Leadership behavior affects the efficiency of personnel administration in educational institutions. Under the Office of Phra Nakhon Si Ayutthaya Primary Educational Service Area, Region 1, the overall picture was at a high level. The statistical significance at the .05 level consisted of teamwork leadership behavior. middle way leadership behavior People-Oriented Leadership Behavior and low work-oriented, high-oriented leadership behavior Overall, the forecast for the efficiency of personnel administration in educational institutions was 61.90 percent.